2019
DOI: 10.1039/c8tc05982a
|View full text |Cite
|
Sign up to set email alerts
|

Template based sintering of WO3 nanoparticles into porous tungsten oxide nanofibers for acetone sensing applications

Abstract: Porous WO3 nanofibers have been synthesized by electrospinning polyvinylpyrrolidone (PVP) nanofibers embedded with semiconducting WO3 nanoparticles followed by annealing in air and have been tested toward acetone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…This sensing behaviour is correlated with recently reported results. 24,45 Further, it was observed that the sensitivity values for 90% and 95% water were very close, which confirms that saturation level was reached. Thus, 95% water with acetone is considered as an optimized amount because under this condition, any increase in sensitivity is only from acetone.…”
Section: Acetone Sensing Propertiessupporting
confidence: 54%
See 1 more Smart Citation
“…This sensing behaviour is correlated with recently reported results. 24,45 Further, it was observed that the sensitivity values for 90% and 95% water were very close, which confirms that saturation level was reached. Thus, 95% water with acetone is considered as an optimized amount because under this condition, any increase in sensitivity is only from acetone.…”
Section: Acetone Sensing Propertiessupporting
confidence: 54%
“…Here, the developed acetone sensor exhibited detection limits in the range of 10 ppm to 10 ppb. This sensing range is better than that of the recently reported acetone sensors using other metal oxides such as Co-In 2 O 3 (100 ppm), 23 WO 3 (12.5 ppm), 24 Pd-SmFe 1Àx Mg x O 3 (0.5 ppm), 25 Co 3 O 4 (200 ppm), 26 NiO/NiCo 2 O 4 (100 ppm), 27 and Au-ZnO (100 ppm). 28 Due to the low detection limit of the present LaFeO 3 dendrite-based acetone sensor, it could be used to monitor acetone vapour even at trace level (ppb) concentrations.…”
Section: Introductionmentioning
confidence: 68%
“…In Figure 3 the broad absorption peaks at <1000 cm −1 indicate the presence of pure tungsten oxide. The band at 619 cm −1 is attributed to W–O stretching vibration, while bands at 801 and 762 cm −1 are attributed to the inter-bridge stretching O-W-O and the corner-sharing mode W-O-W, respectively [ 44 , 45 ]. Tungsten oxide synthesized from PTA + EtOH sol-gel has much sharper peaks due to a more orderly structure with well-expressed W-O stretching vibration.…”
Section: Resultsmentioning
confidence: 99%
“…The widespread use of low-power UV LEDs to activate the sensor sensitivity of semiconductor oxides has led to increased publication activity in this area since the 2010s. To date, numerous studies have been published on the effect of UV radiation on the activation of the sensor sensitivity of semiconductor oxides, such as SnO 2 [ 35 , 36 ], In 2 O 3 [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ], ZnO [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], WO 3 [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], and TiO 2 [ 60 , 61 , 62 , 63 , 64 ], of various morphologies. Despite the fact that in some cases the obtained materials demonstrated high sensor sensitivity, many authors noted the low selectivity of materials based on individual binary metal oxides.…”
Section: Activation Of Gas Sensitivity Of Semiconductor Metal Oxides Under Uv Lightmentioning
confidence: 99%